A Librarian-Centered Study of Perceptions of Subject Terms and Controlled Vocabulary. Issue 7 (17th November 2017) - Schultz, William N.; Braddy, Lindsay
ABSTRACT: Controlled vocabulary and subject headings in OPAC records have proven to be useful in improving search results. The authors used a survey to gather information about librarian opinions and professional use of controlled vocabulary. Data from a range of backgrounds and expertise were examined, including academic and public libraries, and technical services as well as public services professionals. Responses overall demonstrated positive opinions of the value of controlled vocabulary, including in reference interactions as well as during bibliographic instruction sessions. Results are also examined based upon factors such as age and type of librarian.